Pengaruh dana bagi hasil, dana alokasi umum, dana alokasi khusus, dan pendapatan asli daerah terhadap belanja daerah di bidang pendidikan pada kabupaten dan kota di Provinsi Sumatera Selatan - Ahlillah, Rua Wahyu; Sari , Kartika Rachma; Oktarida, Anggeraini (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds and Local Original Revenue on Regional Expenditures in the Education Sector in Regencies and Cities in South Sumatra Province. This study is focused only on Regencies/Cities in South Sumatra Province. The research data uses secondary data. The research data was obtained from the revenue realization report and Regional Education Balance per Regency/City in South Sumatra Province. The number of samples was 17 Regencies/Cities with a total observation of 85 budget realization reports and Regional Education Balance per Regency/City in South Sumatra Province. The data analysis technique was multiple linear regression with the help of SPSS software version 24. The results of the study showed that the Special Allocation Fund and General Allocation Fund had a positive and significant effect on Regional Expenditures in the Education Sector partially, but the Revenue Sharing Fund and Local Original Revenue did not affect Regional Expenditures in the Education Sector partially. It can be concluded that Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds and Local Original Revenue have a positive and significant effect on Regional Expenditures in the Education Sector simultaneously.